2004
DOI: 10.1097/01.alc.0000134216.22162.a5
|View full text |Cite
|
Sign up to set email alerts
|

Test‐Retest Reliability of Adolescents’ Self‐Report of Substance Use

Abstract: The CRAFFT screen is a reliable means of screening adolescents for substance abuse, although we recommend using the past-year version. The TLFB is a reliable method of quantifying adolescents' alcohol and cannabis use at intervals of 30, 60, or 90 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 102 publications
(72 citation statements)
references
References 24 publications
2
69
1
Order By: Relevance
“…Previous studies have shown self-report to be a valid method for measuring substance use among adolescents, however, and it compares favorably with other methods of substance use detection, such as laboratory testing. 14,61,62 Although there was 25% to 30% loss to follow-up in our New England sample, attrition was similar between groups, both in the rates and the profile of those lost to follow-up, and we found that our results did not change after missing data imputation. Finally, we were unable to assess effects on use of drugs other than cannabis because of insufficient numbers.…”
Section: Discussionmentioning
confidence: 50%
See 3 more Smart Citations
“…Previous studies have shown self-report to be a valid method for measuring substance use among adolescents, however, and it compares favorably with other methods of substance use detection, such as laboratory testing. 14,61,62 Although there was 25% to 30% loss to follow-up in our New England sample, attrition was similar between groups, both in the rates and the profile of those lost to follow-up, and we found that our results did not change after missing data imputation. Finally, we were unable to assess effects on use of drugs other than cannabis because of insufficient numbers.…”
Section: Discussionmentioning
confidence: 50%
“…Providers today face opposing pressures: recommendations to screen patients for more and more problems, and financial realities that require they see more patients quickly. 14,63,64 Use of a computer-facilitated system such as this one may offer a way to improve both patient care and provider efficiency. a New England logistic models for both 3-and 12-month outcomes adjusted for the multisite sampling design; baseline past-12-month substance use; age; gender; parent education level; type of visit (well visit or other); perceived parent, sibling, and peer substance use; provider gender; and connectedness to provider.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…62 Test-retest reliability of the CRAFFT has been shown to be high, especially when the questions are prefaced with the phrase "in the past year" when office-based screening is performed. 63 Recently, the CRAFFT tool use was integrated into an adolescent substance use screening, brief intervention, and referral-to-treatment algorithm and tool kit to augment pediatricians' confidence and ability in responding effectively to screening results. 64 More research is still needed to aid in developing brief intervention strategies (ie, short, efficient, office-based techniques) that health care providers who work with adolescents can use to detect and intervene with alcohol misuse.…”
Section: Role Of the Pediatricianmentioning
confidence: 99%